Evaluation of management of snake bites in a teaching hospital in northern Ghana: a retrospective descriptive study - Yakubu, Abdul-Subulr; Abdul-Mumin, Alhassan; Rivera, Odalys (International Journal Of Community Medicine And Public Health, 2019)
Background: Snakebite is a public health problem afflicting mainly rural farmers. We seek to examine the profile and management of snakebite cases presenting to the Tamale Teaching Hospital of Ghana over a 30-month period. Methods: One hundred and ninety-two cases of snakebites presenting to the Tamale Teaching Hospital over a 30-month period from January 2016 to June 2018 were retrospectively analyzed. Information about the clinical manifestation of the snakebites, treatment instituted as well as the outcome was extracted from patient folders for the analysis. Results: Out of the 192 cases of snakebite, 131 (68.2%) occurred in males. The mean age of the victims was 26.5 years. The major patterns of envenomation were coagulopathy (84.9%) and local swelling/pain (82.8%). The causative snake species was identified in only 11.5% of cases, all of which were vipers. Antivenom was administered in 94.8% of the victims and the average amount administered was 84.64 milliliters (approximately 8 vials). Reaction to antivenoms was observed in 13.5% of cases, comprising mostly minor reactions. Antibiotics were utilized in 99.5% of cases with more than half receiving more than one type of antibiotic. Steroids use was common (62%) whilst 22.9% received antifibrinolytics despite the absence of evidence supporting their use in snakebite. Conclusions: Snakebite is an occupational health hazard of mainly rural farmers. The unwarranted use of non-beneficial medications is still rife. In addition to ensuring the continuous availability of effective antivenoms, there is the need for the development and adherence to protocols that take into consideration the prevailing local conditions.